Nuclear Receptors in Myocardial and Cerebral Ischemia—Mechanisms of Action and Therapeutic Strategies - Joanna Rzemieniec (MDPI AG, 2021)
Nearly 18 million people died from cardiovascular diseases in 2019, of these 85% were due to heart attack and stroke. The available therapies although efficacious, have narrow therapeutic window and long list of contraindications. Therefore, there is still an urgent need to find novel molecular targets that could protect the brain and heart against ischemia without evoking major side effects. Nuclear receptors are one of the promising targets for anti-ischemic drugs. Modulation of estrogen receptors (ERs) and peroxisome proliferator-activated receptors (PPARs) by their ligands is known to exert neuro-, and cardioprotective effects through anti-apoptotic, anti-inflammatory or anti-oxidant action. Recently, it has been shown that the expression of aryl hydrocarbon receptor (AhR) is strongly increased after brain or heart ischemia and evokes an activation of apoptosis or inflammation in injury site. We hypothesize that activation of ERs and PPARs and inhibition of AhR signaling pathways could be a promising strategy to protect the heart and the brain against ischemia. In this Review, we will discuss currently available knowledge on the mechanisms of action of ERs, PPARs and AhR in experimental models of stroke and myocardial infarction and future perspectives to use them as novel targets in cardiovascular diseases.